A Historical Discourse on Tithing and Seed Sowing in some Nigerian Pentecostal Churches - Kitause, R. Habila; Achunike, H. Chukwuka (IOSR Journal of Humanitites and Social Science, 2013)
Nigerian Pentecostal theology of prosperity has always been built around Tithing, Offering and Seed sowing with the attendant spill over effect on the mainline churches becoming more captivated in the practice. Even within the Pentecostal circles, the neo Pentecostals are steadily exerting a great deal of influence on the classical Pentecostals by enticing some of them to start preaching prosperity in the manner that the neo Pentecostals do. This article employs oral interview as well as phenomenological and expository approaches in its studies. It is discovered that prosperity preaching is currently becoming an important religious phenomenon in the Nigerian religious landscape leading to the skyrocketing of prosperity churches in contemporary Nigeria. The article submits that it is high time those who preach prosperity in Nigeria maintained a balance between their prosperity emphasis and salvation messages for the sake of people’s souls.
free